Superior Sulcus Tumors Invading the Spine: Multimodal Treatment Outcomes From the Preimmunotherapy Era - Semih Unal, BS; Ricardo Feller, MD; Agnita Stadhouder, MD; David.J. Heineman, MD, PhD; Timothy U. Jiya, MD; Martijn van Dorp, MD; Idris Bahce, MD, PhD; Jerry Braun, MD, PhD; Suresh Senan, MD, PhD; Max Dahele, MBChB., PhD; Chris Dickhoff, MD, PhD (JTO Clinical and Research Reports, 2023)
Introduction: Curative-intent treatment of superior sulcus tumors (SSTs) of the lung invading the spine presents considerable challenges. We retrospectively studied outcomes in a single center, uniformly staged patient cohort treated with induction concurrent chemoradiotherapy followed by surgical resection (trimodality therapy). Methods: An institutional surgical database from the period between 2002 and 2021 was accessed to identify SSTs in which the resection included removal of at least part of the vertebral body. All patients were staged using fluorodeoxyglucose positron emission tomography (/computed tomography), computed tomography scan of the chest/upper abdomen, and brain imaging. Surgical morbidity was assessed using the Clavien-Dindo classification. Overall and disease-free survival were calculated using the Kaplan-Meier method. Results: A total of 18 patients were included: 8 complete and 10 partial vertebrectomies were performed, with six of the eight complete vertebrectomies involving two vertebral levels, resulting in Complete surgical resection (R0) in 94%. Nine patients had a 1-day procedure, and nine were staged over 2 days. The median follow-up was 30 months (interquartile range 11–57). The 90-day postoperative morbidity was 44% (grade III/IV), with no 90-day surgery–related mortality. There were 83% who had a major pathologic response, associated with improved survival (p = 0.044). The 5-year overall and disease-free survival were 55% and 40%, respectively. Disease progression occurred in 10 patients, comprising locoregional recurrences in two and distant metastases in eight patients. Conclusions: Multimodality treatment in selected patients with a superior sulcus tumor invading the spine is safe and results in good survival. Such patients should be referred to expert centers. Future research should focus on improving distant control (e.g. [neo]adjuvant immunotherapy).